Exploring the policy process leading to the establishment of the ARF (African Renaissance and International Co-operation Fund) - Brook, Aletta Nomgidi (My University, 2015)
Development aid plays a significant role on the African continent in a number of ways which include, but is not limited to, financing budget deficits, conflict resolution and humanitarian assistance. South Africa, China, India and Brazil are among the “four main South powers” emerging on the global scene with aid policies designed at providing development aid to African Countries [Tjønneland, 2013: 1]. This study has examined the establishment and implementation of the African Renaissance and International Co-operation Fund (ARF) by analysing the policy processes that led to its creation and operation, from 2000 to 2009. The principle behind the development of such an act was South Africa’s desire to show its commitment in assisting in resolving Africa’s socio-economic challenges that impede development in Africa. ARF has suffered inconsistency in policy making and implementation. The study has found that the challenges in ARF policy processes were attributed to governance issues, issues of accountability, temptation to be used as a state fund for political interest, weakness in the institutional framework, absence of autonomy in management, absence of monitoring and evaluation, political power and poor administration systems.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2015.
Keywords: Policy formulation; Policy adoption; Policy implementation; Monitoring and evaluation